Biopterin metabolism and nitric oxide recoupling in cancer - Clark, Gene Chatman; Lai, Alan; Agarwal, Aashri; Liu, Zheng; Wang, Xiang-Yang (Frontiers in Oncology, 2024)
Tetrahydrobiopterin is a cofactor necessary for the activity of several enzymes, the most studied of which is nitric oxide synthase. The role of this cofactor-enzyme relationship in vascular biology is well established. Recently, tetrahydrobiopterin metabolism has received increasing attention in the field of cancer immunology and immunotherapy due to its involvement in the cytotoxic T cell response. Past research has demonstrated that when the availability of BH4 is low, as it is in chronic inflammatory conditions and tumors, electron transfer in the active site of nitric oxide synthase becomes uncoupled from the oxidation of arginine. This results in the production of radical species that are capable of a direct attack on tetrahydrobiopterin, further depleting its local availability. This feedforward loop may act like a molecular switch, reinforcing low tetrahydrobiopterin levels leading to altered NO signaling, restrained immune effector activity, and perpetual vascular inflammation within the tumor microenvironment. In this review, we discuss the evidence for this underappreciated mechanism in different aspects of tumor progression and therapeutic responses. Furthermore, we discuss the preclinical evidence supporting a clinical role for tetrahydrobiopterin supplementation to enhance immunotherapy and radiotherapy for solid tumors and the potential safety concerns.